Memória gráfica de Ijuí/RS: um estudo a partir do almanaque Kalender der Serra-Post - Fischer, Rafael de Siqueira (2024)
This research, presented to the Graduate Program in Cultural Heritage at the Federal University of Santa Maria (UFSM) – thematic area "History and Cultural Heritage" and research line "History and Cultural Heritage" – analyzed the visual language characteristics of the Kalender der Serra-Post and its relation to the socio-historical context of the publication from 1922 to 1931, from the perspectives of material culture and print culture. Specific pages of the publication were selected based on pre-established criteria, resulting in a total of fifty pages. The research methodology was based on the “Methodological set for research in design history from printed materials” (FONSECA; CAMPOS; GOMES, 2016), which is divided into two parallel work fronts: the researcher’s approach to the socio-historical context of the print and the graphic analysis of the print. At the end of the research, it was found that, within the proposed analytical cutouts, the visual language of the Kalender underwent a process of qualitative evolution in its first decade of existence. The composition evolved from simpler forms to aesthetically and technically more elaborate presentations, driven by the technological and social transformations of the immediate context.